Surveys in Social Research / Fourth Edition - De Vaus D.A (Ucl Press, 1996)
This excellent text can be recommended for courses on research design as well as to people requiring an independent source of information about the use of survey data. Preface, The Scope of Survey Research, The Nature of Surveys, Theory and Social Research, Formulating and Clarifying Research Questions, Collecting Data, Developing Indicators for Concepts, Finding a Sample, Constructing Questionnaires, Administering Questionnaires, Analyzing Data, Overview of Analysis, Bivariate Analysis: Crosstabulations, Bivariate Analysis: Alternative Methods, Elaborating Bivariate Relationships, Multivariate Analysis, The Process of Analysis, Coding, Building Scales, Initial Analysis, Moving Beyond Initial Analysis, Putting It Into Practice: A Research Example, Ethics in Survey Research, The Potential of Surveys, Areas of the Normal Curve, Exercises, Glossary, Bibliography, Index.